Current taxonomy of phages infecting lactic acid bacteria - Mahony, Jennifer; Van Sinderen, Douwe (Frontiers in Microbiology, 2014)
Phages infecting lactic acid bacteria have been the focus of significant research attention over the past three decades. Through the isolation and characterization of hundreds of phage isolates, it has been possible to classify phages of the dairy starter and adjunct bacteria Lactococus lactis, Streptococcus thermophilus, Leuconostoc spp. and Lactobacillus spp. Among these, phages of L. lactis have been most thoroughly scrutinized and serve as an excellent model system to address issues that arise when attempting taxonomic classification of phages infecting other LAB species. Here, we present an overview of the current taxonomy of phages infecting LAB genera of industrial significance, the methods employed in these taxonomic efforts and how these may be employed for the taxonomy of phages of currently underrepresented and emerging phage species.